2021
DOI: 10.1038/s41591-021-01553-w
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor DNA-guided treatment with pertuzumab plus trastuzumab for HER2-amplified metastatic colorectal cancer: a phase 2 trial

Abstract: The applicability of circulating tumor DNA (ctDNA) genotyping to inform enrollment of patients with cancer in clinical trials has not been established. We conducted a phase 2 trial to evaluate the efficacy of pertuzumab plus trastuzumab for metastatic colorectal cancer (mCRC), with human epidermal growth factor receptor 2 (HER2) amplification prospectively confirmed by tumor tissue or ctDNA analysis (UMIN000027887). HER2 amplification was confirmed in tissue and/or ctDNA in 30 patients with mCRC. The study met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(90 citation statements)
references
References 20 publications
4
75
0
Order By: Relevance
“…Additionally, we did not perform NGS analysis in the matching peripheral blood to verify the consistency of HER2 amplification with tissue. A recent clinical trial showed that identification of the HER2 status by circulating tumor DNA (ctDNA) showed similar accuracy to conventional tissue genotyping ( 23 ). Although this suggests that ctDNA has good application value in identifying patients who benefit from the dual-HER2 blockade and monitor treatment response, it is still necessary to conduct a large number and detailed comparative analyses on the expression profile of HER2 in tissues and ctDNA and to comprehensively judge the clinical applicability of ctDNA genotyping on HER2 amplification.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we did not perform NGS analysis in the matching peripheral blood to verify the consistency of HER2 amplification with tissue. A recent clinical trial showed that identification of the HER2 status by circulating tumor DNA (ctDNA) showed similar accuracy to conventional tissue genotyping ( 23 ). Although this suggests that ctDNA has good application value in identifying patients who benefit from the dual-HER2 blockade and monitor treatment response, it is still necessary to conduct a large number and detailed comparative analyses on the expression profile of HER2 in tissues and ctDNA and to comprehensively judge the clinical applicability of ctDNA genotyping on HER2 amplification.…”
Section: Discussionmentioning
confidence: 99%
“…The concordance of HER2 amplification results between tissue-based testing and blood-based ctDNA testing was noted to be 83%. 41 The confirmed ORR was 30% in patients with tissue-based confirmatory testing with positive HER2 amplification and 28% among patients with HER2 amplification determined by ctDNA. For patients with positive tissue confirmation, the median PFS was 4.0 months, the median OS was 10.1 months, and the median PFS and OS were 3.1 months and 8.8 months for patients with ctDNA testing, respectively.…”
Section: The Triumph Trialmentioning
confidence: 90%
“…Another good example of ctDNA application is in HER2 amplified disease. Recent prospective trials have suggested that plasma HER2 amplifications predict response to HER2-directed therapies such as lapatinib, trastuzumab, pertuzumab, and fam-trastuzumab deruxtecan-nxki (T-DXd) [ 136 139 ]. For example, better responses to T-DXd in gastric cancers were seen when plasma HER2 and higher copy number amplifications were detected [ 138 ].…”
Section: Molecular Profiling In the Bloodmentioning
confidence: 99%
“…For example, better responses to T-DXd in gastric cancers were seen when plasma HER2 and higher copy number amplifications were detected [ 138 ]. Also, changes in plasma copy number during HER2-directed therapy were associated with therapeutic response and survival in upper GI cancers and CRCs [ 122 , 136 , 137 , 139 ]. Baseline and emerging resistance mutations detected in the plasma at the time of progression, such as MYC , EGFR , FGFR2 , and MET amplification, have also been reported along with promising therapeutic strategies to overcome resistance, including combining anti-HER2 and other targeted or immune therapies [ 136 , 139 ].…”
Section: Molecular Profiling In the Bloodmentioning
confidence: 99%